Confirmation Bias Analysis of Religious Intolerance Trends: A Study of the Views of Lecturers at Religious-Based Universities in Yogyakarta - Setyowati, Endah; Sigalingging , Hendra (Faculty of Theology Duta Wacana Christian University, 2025)
AbstrakPenelitian ini bertujuan untuk menganalisis peran Bias Konfirmasi dalam menentukan sikap dan perilaku intoleransi beragama menurut dosen universitas agama di Yogyakarta. Konsep Bias Konfirmasi merupakan salah satu pendekatan kontribusi Neuroscience yang dapat digunakan untuk memahami fenomena sosial seperti sikap dan perilaku intoleransi dalam konteks masyarakat dengan keberagaman agama. Melalui survei yang dilanjutkan dengan wawancara mendalam kepada informan, penelitian ini memberikan gambaran mengenai pandangan para informan dalam menciptakan sikap intoleransi beragama. Sikap penerimaan terhadap keberadaan agama yang berbeda menghilangkan bias konfirmasi terhadap berita konflik yang menggunakan identitas agama. Namun pada situasi tekanan kelompok, bias konfirmasi berkaitan dengan sesuatu yang tidak pernah ada dalam ingatan berpotensi menimbulkan sikap atau perilaku intoleran. AbstractThis study aims to analyze the role of Confirmation Bias in determining the attitude and behavior of religious intolerance according to the lecturers of religiously affiliated universities in Yogyakarta. The concept of Confirmation Bias is one of the approaches contributed by Neuroscience that can be used to understand social phenomena such as intolerant attitudes and behavior in the context of societies with religious diversity. Through a survey followed by in-depth interviews, this research provides an overview of the informants’ views on creating attitudes of religious intolerance. An attitude of acceptance towards the existence of different religions eliminates confirmation bias towards conflict news that uses religious identities. However, in situations of group pressure, confirmation bias is related to something that has never been in memory which has the potential to give rise to intolerant attitudes or behavior.